On the Particular Applicability and Usefulness of Relational Data Base Systems for the Management and Analysis of Medical Data - Hill, Claire L. (1981)
This paper concerns the application of relational database systems to medical data. Database management systems are defined, and the major types - hierarchical, network, and relational - are discussed. Three applications of relational systems at the Massachusetts General Hospital are described: (1) development of online data systems in the Primary Care Program and in an affiliated health center, (2) aggregation of various data for analysis of patient utilization patterns, and (3) revision of an existing data system in the hospital's tumor registry. The authors recommend the relational approach to data management because relational systems provide flexible tools for database design and modification, facilitate the aggregation of data from many sources, and permit creation of disciplined databases that are analyzable from many angles.